Gamelan Music and Physiological Responses in Patients with Ventilator Support - Suhartini Suhartini; Charuwan Kritpacha; Ploenpit Thaniwattananon (MEDIA MEDIKA INDONESIANA, 2012)
Background: Music is a non-pharmacological nursing intervention that can be used complementarily in the care of patients receiving ventilator support. The study aim was to explore the effects of music intervention on physiological responses for patients receiving ventilator support in intensive care units in Indonesia.Methods: It was a quasi experimental study using a non-equivalent control group and pre-test/post-test design. Forty subjects were assigned into either a control or experimental group (20 subjects/group). The outcome measures were physiologic responses, including systolic and diastolic blood pressure, heart rate, and respiratory rate obtained every 10 minutes for 20 minutes of music intervention. Data analysis used Chi-square test, Fisher-exact test, independent t-test, and paired sample t-test.Result: The findings showed that the subjects who received music intervention demonstrated statistically significant reductions in sympathetic physiological responses (p<0.05). Specifically, there was a significant difference in systolic blood pressure, but there was no significant difference in diastolic blood pressure, heart rates, and respiratory rate between the two groups. In the between groups comparison, it was only diastolic blood pressure that showed the reduction of mean score from pretest to posttest in the experimental group and in the control group.Conclusion: Gamelan intervention gives positive impact to patients with ventilator.Keywords: Music intervention, ventilator support, physiological responses ABSTRAK Musik gamelan dan responfisiologi pada pasien dengan ventilatorLatar belakang: Musik adalah intervensi keperawatan secara non farmakologikal yang dapat digunakan secara komplementari dalam merawat pasien yang menggunakan ventilator. Riset ini bertujuan untuk mengeksplorasi efek intervensi musik dalam menurunkan respon fisiologis pasien dengan ventilator di ruang perawatan intensif di Indonesia.Metode: Penelitian adalah penelitian semu dengan rancangan grup kontrol non-equivalen, pre dan post pengukuran. Ada 40 subyek penelitian yang dikelompokkan dalam grup kontrol dan grup eksperimen. Hasil yang diukur adalah tekanan darah sistolik dan diastolik, denyut jantung, dan frekuensi pernafasan, yang didapatkan dari pengukuran setiap 10 menit dalam 20 menit pemberian intervensi musik. Data diukur dengan menggunakan uji Chi-square, uji Fisher-exact, uji t-independen, dan uji t-berpasangan.Hasil: Hasil menunjukkan bahwa subyek yang menerima intervensi musik secara signifikan menurunkan respon simpatetik fisiologis (p<0,05). Secara spesifik, ada perbedaan yang bermakna dalam tekanan darah sistolik, tetapi tidak ada perbedaan yang signifikan dalam tekanan darah diastolik, denyut jantung, dan frekuensi pernafasan diantara kedua grup. Pada kelompok kontrol, hanya tekanan darah diastolik yang menunjukkan menurunkan skor rerata dari pretes ke postes dalam grup eksperimen dan grup kontrol.Simpulan: Intervensi gamelan memberi dampak positif pada pasien dengan ventilator